Supporting 21st-Century Learning by Providing Educational Infrastructure in the Form of Land: Legal Perspective - Nurdin, Zefrizal (Universitas Islam Negeri Raden Intan Lampung, 2021)
Land as school infrastructure is often neglected in the certification process. This research emphasized that school land certification is essential and whether it automatically includes authority over everything on it, what land rights can be given to the school, and how it is carried out. This research used the normative juridical research method by leaning on empirical research. Secondary data taken from library research dominates this research. The data was obtained through document studies or library studies. Furthermore, some primary data was obtained through observations. Land certificates is a piece of solid evidence to ascertain the rights of the education provider as the subject of rights so that they can defend their rights from claims by other parties. However, it does not automatically cover all authority over what is on the land because it is a part of the horizontal separation principle. School land can have the status of State land and can also have four types of land rights owned by the education providers, namely Freehold Title, Building Right Title, Cultivation Right Title, and Mortmain (Waqf) right. The rights can be obtained through sporadic registration or complete systematic land registration. The availability and readiness of facilities and infrastructure are essential in 21st-century education and learning because they will significantly affect learning.